DURABILITAS CAMPURAN AC-WC MENGGUNAKAN BATU GUNUNG BABA, TANA TORAJA - Louise Elizabeth Radjawane (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2023)
The decline in road service conditions in the form of road damage can be caused by water due to high rainfall so that it enters the pavement layer. This study aims to determine the durability or resistance of the AC-WC mixture using Mount Baba stone. By using the Marshall test method, the results obtained through the Marshall immersion test with variations in immersion time from 0.5 hours - 60 hours, namely the durability value of 95.02 % - 86 34%. Thus, there is a decrease in the durability of the mixture with the duration of the immersion time. This is due to the large number of cavities and pores filled with water, the mixture becomes impermeable or easily damaged.